Effect of ethanol extract of Irvingia Gabonensis (Aubrey Lecomte Ex O. Rorke) baill. (Irvingiaceae) seeds on diet induced obesity in Wistar Rats (2021)
Obesity is a chronic condition associated with high morbidity and mortality rates. Its comorbidities include cancer, diabetes mellitus, and cardiovascular diseases. Traditional medicines have found increasing use due to cost effectiveness and mini mal side effects. This study evaluated the Anti-obesity effect of ethanolic extract of Irvingia gabonensis seeds. Wistar rats were divided into control and treatment groups. Untreated group I on normal diet (negative control), untreated group II on high fat diet (HFD) and 10 mL/Kg Tween 80 (positive control), extract treated groups III-V (50, 100 and 200 mg/Kg) on HFD. Orlistat treated group VI (200 mg/Kg) on HFD (standard). Body mass index (BMI), weight of abdominal fat, cholesterol levels and hepatic enzymes were evaluated after 12 days of treatment. Body mass index (BMI) and abdominal fat of (treatment groups) reduced. How ever, the seed extract and orlistat did not significantly increase liver enzymes. Conclusion: Irvingia gabonensis seed extract showed anti-obesity properties.